2022
DOI: 10.3389/fphar.2022.874696
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Quercetin Inhibits Tumorigenesis of Colorectal Cancer Through Downregulation of hsa_circ_0006990

Abstract: Quercetin can significantly inhibit the progression of colorectal cancer (CRC). However, its specific mechanism remains largely unclear. In this study, we aimed to explore the correlation among quercetin, tumour-associated macrophages (TAMs) and circular RNAs (circRNAs) in the progression of CRC and to present a novel strategy for the treatment of CRC. In this study, we revealed that quercetin could suppress the autophagy of M2-TAMs and induced their differentiation into M1-TAMs, by which quercetin significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the study of I. W. Cheuk, resveratrol enhanced chemosensitivity by reversing macrophage polarization in breast cancer 57 . Quercetin can inhibit the autophagy of M2-TAMs and induce their differentiation to M1-TAMs, thus inhibiting the proliferation of colorectal cancer cells 58 . Studies by Jincheng Wang et al have found that curcumin is synergistic with cisplatin in the treatment of osteosarcoma by inhibiting M2-like polarization of tumor-associated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of I. W. Cheuk, resveratrol enhanced chemosensitivity by reversing macrophage polarization in breast cancer 57 . Quercetin can inhibit the autophagy of M2-TAMs and induce their differentiation to M1-TAMs, thus inhibiting the proliferation of colorectal cancer cells 58 . Studies by Jincheng Wang et al have found that curcumin is synergistic with cisplatin in the treatment of osteosarcoma by inhibiting M2-like polarization of tumor-associated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is a dietary flavonoid with antioxidant, anti-inflammatory and anticancer properties. According to related studies, quercetin inhibits the tumorigenesis of CRC by inhibiting the polarization of M2 macrophages and downregulating hsa_circ_0006990 ( Chen et al, 2022a ). As a drug, quercetin has also been studied for use in combination with drug delivery systems for the treatment of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin (QR) is a avonoid found in foods that is particularly abundant in onions [21]. QR has previously been reported to have protective properties against autophagy caused by M2 tumor-associated macrophages [22]. Also, QR has been shown to suppress autophagy and promote apoptosis to prevent the formation of neutrophil extracellular traps and neutrophil activitiesaccording to the experiments in rats with rheumatoid arthritis [23].…”
Section: Introductionmentioning
confidence: 99%